Gambaran Tingkat Stres, Kecemasan, dan Depresi pada Penderita Kanker Payudara yang Menjalani Kemoterapi di Ruang Gili Asahan RSUD Provinsi NTB - I Made Eka Santosa; Nazamuddin; Endy Bebhasari AP; Wahyu Cahyono; Ni Made Sumartyawati (LPPM STIKES Mataram, 2023)
Introduction: Breast cancer is the highest disease to attack women comparing to other cancers in Indonesia. Breast is an important organ of women. Besides for breast milk this organ is attracting sexual organ. Anytime breast has problem, the psychological factor should be closely paid attention specifically since the mental-emotional condition of women may be unstable so that it may cause psychiatric complication as stress, anxiety, and depression. That is way it is important to identify psychiatric problems. Purpuse: This research is aimed at determining the description of stress level, anxiety, and depression of patients with breast cancer. Methods: This research is descriptive study. The samples were 62 respondents with breast cancer selected through purposive sampling. They are conducting chemotherapy in provincial hospital of NTB. The data were collected through questionnaires of Depression Anxiety Stress Scale (DASS) consisting of 42 questions. Result: From this research, it was found that 38.71% of respondents experienced stress, 54.84% experienced anxiety, 25.81% of respondents experienced depression. Suggestions: for future researchers are that they can carry out further research related to anemia in patients with kidney failure. Key Word : Stress, anxiety, depression, breast cancer, chemotherapy